Decolonising the curriculum: Southern interrogations of time, place and knowledge - Catherine Manathunga (University of Johannesburg, 2018)
Despite decades of postcolonial, Indigenous and feminist research, dominant Northern knowledge continues to claim universality across time and space in many academic disciplines and continues to ignore geopolitical power struggles over knowledge. This has taken on a particular urgency in South Africa since the #RhodesMustFall and #FeesMustFall student campaigns beginning in 2015. The international Scholarship of Teaching and Learning (SOTL) field has only begun to grapple with the implications of Southern theory for teaching and learning. In this article, I focus on Southern interrogations about time, place and knowledge and what they offer us in terms of decolonising the curriculum and southernising SOTL. I apply these theoretical resources to the need to trouble taken-for-granted knowledge hierarchies between Northern and Southern knowledge and argue for a truly dialogic knowledge exchange and redistribution of epistemological privilege. I illustrate how these theoretical resources can be applied to the site of intercultural postgraduate supervision and conclude by extrapolating the implications of this theoretical work to efforts to decolonise the undergraduate and postgraduate university curriculum. How to cite this article: MANATHUNGA, Catherine. Decolonising the curriculum: Southern interrogations of time, place and knowledge. Scholarship of Teaching and Learning in the South, v. 2, n. 1, p. 95-111, Apr. 2018. Available at: http://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=23 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/